2023
DOI: 10.1111/evj.13937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cartilage injury in horses with osteochondral fragments in the metacarpo−/metatarsophalangeal joint: A study on 823 arthroscopies

Abstract: BackgroundOsteochondral fragment removal is commonly performed but there are little scientific data supporting this procedure in the absence of clinical signs. More information is needed to facilitate clinical decision‐making regarding fragment removal of the metacarpo−/metatarsophalangeal joint.ObjectivesTo assess prevalence of cartilage injury in the equine metacarpo−/metatarsophalangeal joint and its association to fragment size, location, age and lameness.Study designRetrospective observational study.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…16 This observation supports the study performed by Goldkuhl in 2023, where Warmbloods older than 7 years were more likely to have articular cartilage damage than juveniles with metacarpophalangeal joint osteochondral fragments. 17 Furthermore, this study identified lesions on the sagittal ridge and dorsal proximal P1 were significantly more likely to have cartilage lesions compared with palmar/plantar P1 fragments. Their conclusions were similar and related to the stabilised embedded nature of the osteochondral fragments in the palmar/plantar pouch.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…16 This observation supports the study performed by Goldkuhl in 2023, where Warmbloods older than 7 years were more likely to have articular cartilage damage than juveniles with metacarpophalangeal joint osteochondral fragments. 17 Furthermore, this study identified lesions on the sagittal ridge and dorsal proximal P1 were significantly more likely to have cartilage lesions compared with palmar/plantar P1 fragments. Their conclusions were similar and related to the stabilised embedded nature of the osteochondral fragments in the palmar/plantar pouch.…”
mentioning
confidence: 65%
“…16 Another study analysed subsequent cartilage injury apparent in mainly Warmbloods with metacarpophalangeal joint osteochondral fragments. 17 These papers expand the field of interest and move the focus away from solely Thoroughbreds. In contrast to other OCD fragments where synovial inflammation has been reported, palmar/plantar osteochondral fragments seem not to, and indicated surgery in unproven juveniles can be delayed.…”
mentioning
confidence: 99%
See 1 more Smart Citation